2021
DOI: 10.3233/jad-201170
|View full text |Cite
|
Sign up to set email alerts
|

Education Exerts Different Effects on Cognition in Individuals with Subjective Cognitive Decline and Cognitive Impairment: A Population-Based Study

Abstract: Background: Education plays a potential important effect on the prevalence and incidence of dementia. However, most of the evidence based on convenience sampling. Objective: To explore effects of education on cognition in individuals with subjective cognitive decline (SCD) and cognitive impairment (CI) from a population-based study. Methods: We examined the effect of education on cognition among individuals with SCD (n = 451) and CI (n = 280) from a population-based study. A series of neuropsychological tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
2
6
2
Order By: Relevance
“…Besides, the higher the level of education, the higher the probability of normal cognitive function. A recent study found that higher educational attainment may delay cognitive decline (20), which was also supported by our study, High levels of education broaden the brain's information base, which in uences cognitive performance (21). Such observation suggests that more attention should be paid to the elderly depressed persons.…”
Section: Discussionsupporting
confidence: 87%
“…Besides, the higher the level of education, the higher the probability of normal cognitive function. A recent study found that higher educational attainment may delay cognitive decline (20), which was also supported by our study, High levels of education broaden the brain's information base, which in uences cognitive performance (21). Such observation suggests that more attention should be paid to the elderly depressed persons.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, education level was not associated with latent class membership. Prior studies have reported that high educational attainment is closely related to cognitive decline in individuals with subjective cognitive decline 55 56. Based on the differences in our findings compared with prior studies, we posit that education level may not affect the distinct symptoms but may have an association with the prevalence of subjective cognitive decline.…”
Section: Discussioncontrasting
confidence: 72%
“…People with low levels of education also demonstrated low cognitive scores. Given the effects of education on cognitive impairment [ 41 , 42 ], better cognitive function could be achieved through marked improvements in educational attainment.…”
Section: Discussionmentioning
confidence: 99%